2015
DOI: 10.11002/kjfp.2015.22.2.267
|View full text |Cite
|
Sign up to set email alerts
|

Quality characteristics and antioxidant activity of onion peel extracts by extraction methods

Abstract: This study was conducted to evaluate the antioxidant activities and the quality characteristics of 70% ethanol extracts from onion peels with different extraction methods (autoclave extraction, AE; low temperature high pressure extraction, LTPE; reflux extraction, RE; and stirrer extraction, SE). The yields of AE, LTPE, RE and SE were 9.00%, 5.39%, 13.21% and 12.41%, respectively. The total polyphenol and flavonoid contents in the AE were significantly higher than in the other extracts. The DPPH radical scaven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
1
1
Order By: Relevance
“…OS extract in DPPH radical scavenging activity showed significant increase in a dose dependent manner. Previous research reported that DPPH radical scavenging activity of OS ethanolic extract was 28.39% at 1 mg/mL [ 27 ], while it was 46.89% at the same concentration in our study. OS extracts produced by ethanol, hot water, and subcritical water showed the different DPPH radical scavenging activities with 72.25%, 49.68%, and 64.72%, respectively [ 22 ].…”
Section: Resultscontrasting
confidence: 47%
See 1 more Smart Citation
“…OS extract in DPPH radical scavenging activity showed significant increase in a dose dependent manner. Previous research reported that DPPH radical scavenging activity of OS ethanolic extract was 28.39% at 1 mg/mL [ 27 ], while it was 46.89% at the same concentration in our study. OS extracts produced by ethanol, hot water, and subcritical water showed the different DPPH radical scavenging activities with 72.25%, 49.68%, and 64.72%, respectively [ 22 ].…”
Section: Resultscontrasting
confidence: 47%
“…ABTS radical scavenging activity of OS increased in a dose-dependent manner. ABTS radical scavenging activity of OS ethanolic extraction was 33.29% in 1 mg/mL [ 27 ]. The high contents of total polyphenol in Indian OS cultivars showed the high antioxidant activities in DPPH and ABTS assays [ 13 ].…”
Section: Resultsmentioning
confidence: 99%